2005
DOI: 10.1093/humrep/deh657
|View full text |Cite
|
Sign up to set email alerts
|

Human sperm chemotaxis: both the oocyte and its surrounding cumulus cells secrete sperm chemoattractants

Abstract: These observations suggest that sperm chemoattractants are secreted not only prior to ovulation within the follicle, as earlier studies have demonstrated, but also after oocyte maturation outside the follicle, and that there are two chemoattractant origins: the mature oocyte and the surrounding cumulus cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 28 publications
2
99
0
4
Order By: Relevance
“…It is widely acknowledged that spermatozoa in the human female reproductive tract have close and prolonged contact with a significant array of NO-producing cells (Rosselli et al 1998, Sun et al 2005, Machado-Oliveira et al 2008; the exact sites of NO production in the female genital tract remain to be investigated, but Machado-Oliveira et al (2008) showed that detectable amounts of NO are produced in human cumulus fragments and oviduct explants. This free radical is relatively unreactive, and is able to diffuse from the cell in which it is generated to the neighbor cells, covering long distances in a very short time (Krö ncke et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that spermatozoa in the human female reproductive tract have close and prolonged contact with a significant array of NO-producing cells (Rosselli et al 1998, Sun et al 2005, Machado-Oliveira et al 2008; the exact sites of NO production in the female genital tract remain to be investigated, but Machado-Oliveira et al (2008) showed that detectable amounts of NO are produced in human cumulus fragments and oviduct explants. This free radical is relatively unreactive, and is able to diffuse from the cell in which it is generated to the neighbor cells, covering long distances in a very short time (Krö ncke et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm chemotaxis plays an essential role in species with external fertilization (Friedrich and Jülicher, 2007) and has been demonstrated to occur also in mammals (Sun et al, 2005). The process takes place in the proximity of the fertilization site and it is initiated by the release of factors from the oocyte and the surrounding cumulus cells.…”
Section: P-induced Sperm Chemotaxismentioning
confidence: 99%
“…Although the attractants and the molecular mechanism of sperm chemotaxis in mammals are not yet known, sperm chemotaxis to follicular fluid, the mature oocyte and the surrounding cumulus oophorus have been reported by a number of studies (Jeon et al, 2001;Wang et al, 2001;Sun et al, 2005;Gil et al, 2008;Guidobaldi et al, 2008;Oren-Benaroya et al, 2008). It has been postulated that the chemoattractants, including heparin, progesterone, atrial natriuretic peptide (ANP), adrenaline, oxytocin, calcitonin and acetylcholine, might also be originated from the cumulus oophorus (Sliwa, 1993;Sliwa, 1994;Anderson et al, 1995;Sliwa, 1995;VillanuevaDíaz et al, 1995).…”
Section: Chemoattractants Released From Cumulus Cellsmentioning
confidence: 99%